2020
DOI: 10.3390/catal10060603
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Post-Treatments to Enhance the Water Stability of NH2-MIL-125(Ti)

Abstract: NH2-MIL-125(Ti) is a metal organic framework (MOF) based on Ti-oxo-clusters widely investigated in water-related applications. Such applications require MOFs with an excellent stability in the aqueous phase, but, despite this, the extent of MOFs’ degradation in water is still not yet fully understood. In this study, we report a quantitative study of the water stability of NH2-MIL-125(Ti), analyzing the ligand release along the contact time in water. This study demonstrates that NH2-MIL-125(Ti) easily leached o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…The N 2 adsorption–desorption isotherms of MIL-125-NH 2 , HCl/MIL-125-NH 2 , and RuO 2 /MIL-125-NH 2 samples (1) and (2) (Figure a) showed an overall type II behavior, following the International Union of Pure and Applied Chemistry classification. This behavior has been reported already for MIL-15-NH 2 and is in line with its microporous character. , At the same time, different behaviors for the two RuO 2 /MIL-125-NH 2 samples and the HCl/MIL-125-NH 2 sample in contrast to the pristine MIL-125-NH 2 at higher pressures were observed. The appearance of a small hysteresis between the adsorption and desorption traces for these three samples is consistent with the presence of mesopores in increasing magnitudes along the series HCl/MIL-125-NH 2 < RuO 2 /MIL-125-NH 2 (1) < (2).…”
Section: Resultssupporting
confidence: 76%
“…The N 2 adsorption–desorption isotherms of MIL-125-NH 2 , HCl/MIL-125-NH 2 , and RuO 2 /MIL-125-NH 2 samples (1) and (2) (Figure a) showed an overall type II behavior, following the International Union of Pure and Applied Chemistry classification. This behavior has been reported already for MIL-15-NH 2 and is in line with its microporous character. , At the same time, different behaviors for the two RuO 2 /MIL-125-NH 2 samples and the HCl/MIL-125-NH 2 sample in contrast to the pristine MIL-125-NH 2 at higher pressures were observed. The appearance of a small hysteresis between the adsorption and desorption traces for these three samples is consistent with the presence of mesopores in increasing magnitudes along the series HCl/MIL-125-NH 2 < RuO 2 /MIL-125-NH 2 (1) < (2).…”
Section: Resultssupporting
confidence: 76%
“…On note, our Al-PMOF­(Fe) photocatalyst is superior to NH 2 -MIL-125­(Ti) in terms of stability. A recent study demonstrated that NH 2 -MIL-125­(Ti) would easily leach out and experience framework degradation in water, thus losing reusability as a photocatalyst. In contrast, our Al-PMOF­(Fe) exhibits good hydrolytic stability thanks to the robust aluminum metal cluster nodes in NRR, thereby imparting high reusability of Al-PMOF­(Fe) as a photocatalyst, which will be discussed below.…”
Section: Results and Discussionmentioning
confidence: 99%
“…434 to its instability under the optimized experimental conditions. 434,435 In any case, considering any possible commercial implementation of MOFs, it is important to assess the long-term photostability under solar light and outdoor conditions, determining the main reasons for photocatalytic activity decay and devising doable reactivation methods.…”
Section: Photocatalyst Stabilitymentioning
confidence: 99%